2019
DOI: 10.3390/medicina55070355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Point-of-Care Ultrasonography and Radiography in the Diagnosis of Long-Bone Fractures

Abstract: Background and objectives: In this study, the accuracy of point-of-care ultrasonography (POCUS) was compared to radiography (XR) in the diagnosis of fractures, the determination of characteristics of the fractures, and treatment selection of fractures in patients admitted to the emergency department (ED) due to trauma and suspected long bone (LB) fractures. Materials and Methods: The patients were included in the study, who were admitted to ED due to trauma, and had physical examination findings suggesting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
2
8
0
1
Order By: Relevance
“…Other studies have reported that ultrasound is more sensitive than radiography to detect rib fractures 16–18 . Similar results were also found with the use of ultrasound in pediatric traumatic injuries, 19–22 although no cases of abuse were considered in those studies.…”
Section: Discussionsupporting
confidence: 72%
“…Other studies have reported that ultrasound is more sensitive than radiography to detect rib fractures 16–18 . Similar results were also found with the use of ultrasound in pediatric traumatic injuries, 19–22 although no cases of abuse were considered in those studies.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the sensitivity of XR imaging in identifying two simultaneous bone fractures was reported as 56%, while the specificity was reported as 94%; the sensitivity in identifying trimalleolar fractures was reported as 17%, and the specificity was reported as 100% [5]. In another study investigating 205 patients with long bone traumas, nine patients had radius and ulna, and one patient had tibia and fibula; in addition to the long bone fracture, two patients had patella fractures, one patient had clavicula fractures, and one patient had calceneus fractures [12]. In a similar study investigating metatarsal fractures in 72 patients, multiple metatarsal fractures were detected in four patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies comparing the imaging methods in the literature. Some of these studies are about comparing the imaging methods, which are: XR and magnetic resonance imaging (MRI) [1,10], XR imaging and ultrasonography (USG) [11,12,13,14,15,16], USG and CT scan [17], CT scan and MRI [18], USG and MRI [19], and some are about XR imaging and CT scans [3,5,8,9,20,21,22]. A small number of the studies comparing XR imaging and CT scanning examine the knee joint.…”
Section: Introductionmentioning
confidence: 99%
“…Zahlreiche Arbeiten belegen den sinnvollen Einsatz der Sonographie in der Akuttraumatologie bei Kindern und Jugendlichen [ 2 , 27 , 32 , 51 ]. Sowohl lange Röhrenknochen, hier besonders der proximale Humerus und der Ellenbogen [ 10 , 22 , 44 ], speziell auch der Unterarm und distaler Radius [ 8 , 36 ] und Frakturen der Klavikula [ 27 ] eignen sich gut für den sonographischen Frakturnachweis. Auch in den USA wird in den letzten Jahren mehr und mehr in der Notfallbehandlung die Sonographie als „point-of-care ultrasonography“ (POCUS) eingesetzt [ 3 ].…”
Section: Diskussionunclassified